The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11904-018-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Serious Non-AIDS Conditions in HIV: Benefit of Early ART

Abstract: Data from the two trials demonstrated that initiating ART early in the course of HIV infection resulted in marked reductions in the risk of opportunistic diseases and invasive bacterial infections. This indicates that HIV causes immune impairment in early infection that is remedied by controlling viral replication. Intriguingly, in START, a marked reduction in risk of cancers, both infection-related and unrelated types of cancers, was observed. Like the findings for opportunistic infections, this anti-cancer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 55 publications
1
17
0
5
Order By: Relevance
“…NEATON;2018). Assim, evitando o desenvolvimento da doença e suas complicações, como as infecções oportunistas levando ao óbito.…”
unclassified
“…NEATON;2018). Assim, evitando o desenvolvimento da doença e suas complicações, como as infecções oportunistas levando ao óbito.…”
unclassified
“…El impacto del Programa TARGA en el análisis de STI reveló que, por cada año transcurrido posterior a su introducción, ocurrió una disminución sustancial en los casos nuevos de 1983 1985 1987 1989 1991 1993 1995 1997 1999 2001 2003 2005 2007 2009 (13). Sin embargo, se ha ido adelantando su comienzo con cortes cada vez más altos de CD4 (350 y 500 células/mm 3 ) como se recomendó luego (17,18) a sabiendas de que el tratamiento universal reduce el riesgo de progresión de la infección (15). Esta forma temprana de tratamiento es el principal impulsor de la reducción de la morbilidad y la mortalidad por sida (16,17,19).…”
Section: Discussionunclassified
“…El inicio de TARV en un estadio avanzado se asocia con una mayor toxicidad medicamentosa y con el síndrome de reconstitución inmune (14). Sin embargo, el inicio del tratamiento se ha adelantado de manera progresiva, con recuentos cada vez más altos de T CD4 (350 y 500 células/mm 3 ), lo que reduce el riesgo de progresión de la enfermedad (15,16). Desde el 2016, la OMS recomienda el tratamiento universal a todas las personas con VIH cualquiera sea el recuento de CD4 (17).…”
Section: Palabras Claveunclassified
“…It has been suggested that in the early stages of HR HPV-induced carcinogenesis the HR HPV-infected cells suppress acute inflammation in the epithelium, while later on HR HPVtransformed cells initiate chronic stromal inflammation, led by an increase of IL-6 158 . Meanwhile, as mentioned earlier, HIV-infection is associated with persistent immune activation and inflammation, illustrated by increased levels of immunologic biomarkers (such as IL-6) that remain increased even after ART is initiated, although at lower levels 28,[158][159][160][161] . Thus, HIV-induced inflammation, not only reduced CD4 counts, may play an important role in cervical cancer development in WLWH and this role may be diminished although not eradicated with suppressive ART.…”
Section: Regarding the Role Of Artmentioning
confidence: 99%